Human epidermal receptor family inhibitors in patients with ERBB3 mutated cancers: Entering the back door. (March 2018) - Verlingue, Loic; Hollebecque, Antoine; Lacroix, Ludovic; Postel-Vinay, Sophie; Varga, Andrea; El Dakdouki, Yolla; Baldini, Capucine; Balheda, Rastilav; Gazzah, Anas; Michot, Jean-Marie; Marabelle, Aurélien; Mir, Olivier; et al.
Abstract: Introduction: Therapeutic inhibition of the human epidermal receptor 3 (ERBB3, HER3) has been challenged by the low frequency of ERBB3 somatic alterations across cancer types. We have evaluated the clinical utility to use available inhibitors of the HER family in the context of ERBB3 mutations. Patients and methods: In this study, we have selected patients with somatic ERBB3 alterations detected in their tumours from the molecular screening programs running at our institution. Techniques used for molecular screening were targeted next generation sequencing, comparative genomic hybridisation and/or whole exome sequencing on fresh frozen tumour biopsies. Results: On the 844 patients with a molecular portrait of their tumours, 31 (3.7%) had a somatic mutation of ERBB3 . Overall, 9 patients received available inhibitors of HER family, including trastuzumab and/or lapatinib or afatinib. Sixteen patients received other molecularly targeted agents, including the Mammalian Target Of Rapamycin (mTOR), the Phosphatidylinositol-4, 5-Bisphosphate 3-Kinase (PI3K) or NOTCH inhibitors or chemotherapy, and 4 patients failed being treated. Thirteen different histological subtypes were affected by ERBB3 mutations; top ones were colorectal carcinomas (6 patients), non-small cell lung cancers (4 patients, including a squamous cell carcinoma), head and neck squamous cell carcinomas (3 patients) and breast carcinomas (3 patients). The presence of a mutation in the tyrosine kinase domain of the ERBB3/HER3 protein detected in four patients' tumours was significantly related to good progression-free survival (hazard ratio [HR] = 0.18, p value = 0.022) and overall survival (HR = 0.19, p value = 0.03) in univariate analysis. Treatment of these four patients included at least a tyrosine kinase inhibitor lapatinib or afatinib. Conclusion: Our exploratory analysis suggests that mutations in the tyrosine kinase domain of the HER3 protein are related to a favourable outcome under HER family inhibitors. Highlights: Targeting ERBB3/HER3 persists to be challenging in oncology. ERBB3 mutations were found in 31 patients' tumours. Available human epidermal receptor family inhibitors including small molecules were administrated to nine patients. Mutations in the tyrosine kinase domain of HER3 were related to better outcome. Selecting patients on ERBB3 alterations may help further drug development.